Low Female Gametophyte Fertility Contributes to the Low Seed Formation of the Diploid Loquat [Eriobotrya Japonica (Thunb.) Lindl.] Line H30-6 - Xia, Qingqing; Dang, Jiangbo; Wang, Peng; Liang, Senlin; Wei, Xu; Li, Xiaolin; Xiang, Suqiong; Sun, Haiyan; Wu, Di; Jing, Danlong; Wang, Shumin; Xia, Yan; et al. (Frontiers in Plant Science, 2022)
Loquat is a widely grown subtropic fruit because of its unique ripening season, nutrient content, and smooth texture of its fruits. However, loquat is not well-received because the fruits contain many large seeds. Therefore, the development of seedless or few-seed loquat varieties is the main objective of loquat breeding. Polyploidization is an effective approach for few-seed loquat breeding, but the resource is rare. The few-seed loquat line H30-6 was derived from a seedy variety. Additionally, H30-6 was systematically studied for its fruit characteristics, gamete fertility, pollen mother cell (PMC) meiosis, stigma receptivity, in situ pollen germination, fruit set, and karyotype. The results were as follows. (1) H30-6 produced only 1.54 seeds per fruit and the fruit edible rate was 70.77%. The fruit setting rate was 14.44% under open pollination, and the other qualities were equivalent to those of two other seedy varieties. (2) The in vitro pollen germination rate was only 4.04 and 77.46% of the H30-6 embryo sacs were abnormal. Stigma receptivity and self-compatibility in H30-6 were verified by in situ pollen germination and artificial pollination. Furthermore, the seed numbers in the fruits of H30-6 did not significantly differ among any of the pollination treatments (from 1.59 ±0.14 to 2 ± 0.17). (3) The chromosome configuration at meiotic diakinesis of H30-6 was 6.87I + 9.99II + 1.07III +0.69IV +0.24V (H30-6), and a total of 89.55% of H30-6 PMCs presented univalent chromosomes. Furthermore, chromosome lagging was the main abnormal phenomenon. Karyotype analysis showed that chromosomes of H30-6 had no recognizable karyotype abnormalities leading to unusual synapsis on the large scale above. (4) The abnormal embryo sacs of H30-6 could be divided into three main types: those remaining in the tetrad stage (13.38%), those remaining in the binucleate embryo sac stage (1.41%), and those without embryo sacs (52.82%). Therefore, we conclude that the loquat line H30-6 is a potential few-seed loquat resource. The diploid loquat line H30-6 was with low gametophyte fertility, which may be driven by abnormal meiotic synapses. The low female gamete fertility was the main reason for the few seeds. This diploid loquat line provides a new possibility for breeding a few-seed loquat at the diploid level.